Analysis of Risky Sexual Behavior in the Drug user Population - Imtiyazi Nabila; Rico Januar Sitorus; Mohammad Zulkarnain (GLOBAL HEALTH SCIENCE GROUP, 2025)
Drug abuse is one of the serious public health problems in Indonesia, especially because it can increase risky sexual behavior for HIV/AIDS transmission. Transmission of HIV can occur not only through the use of injection needles but also through unsafe sexual contact (not using condoms) with fellow injecting drug users or between injecting drug users and FSWs. This study aims to analyze risky sexual behavior in the drug user population at the Palembang City Drug Rehabilitation Center Foundation. This study is a descriptive analytical study with a cross-sectional design. The research instrument used a questionnaire based on the 2023 Integrated Biological and Behavioral Survey (STBP) of the Indonesian Ministry of Health 7. The study sample consisted of 130 people, selected based on the study's inclusion criteria. The majority of respondents were male (100%), age >29 years (63.8%), senior high school (67.7%), unmarried (60.8%), and had a permanent residence (96.2%). Then, the age of first using drugs was 15-19 years (55.4%), with a duration of use >5 years (63.8%), and they did not use injectable drugs (94.6%). From sexual behavior, 56.9% had had sex (vaginal), 28.5% with a permanent female partner, 13.8% with a paid woman. The analysis showed a significant relationship between age, marital status, age of first drug use, and knowledge of HIV/AIDS risk behavior. In contrast, education, current residence status, selling or buying sex, duration of drug use, injection drug use and attitudes were not significantly related. Education efforts and prevention programs need to be more focused on factors that have been proven to have an influence.